Screening of local hyaluronic acid injection modes to increase the efficiency of treating crush injury of soft tissues - I. A. Shperling; A. V. Shulepov; N. V. Shperling; O. Yu. Kuzmina (Бюллетень сибирской медицины, 2022)
Aim. To study the state of microcirculation and metabolic activity of the soft tissues in the compression area in experimental crush injury after local hyaluronic acid injection and to determine the effective mode of its application.Materials and methods. The experiments were carried out on 178 male Wistar rats aged 4–4.5 months and weighing 280–340 g. The study design included anesthesia, modeling of crush injury (CI), local injection of 1.75% hyaluronic acid (HA) solution into the compression area, systemic intravenous injection of 0.9% sodium chloride solution daily for 3 days, and a study of microcirculation and metabolism of the soft tissues in the damaged area 3, 7, 14, and 28 days after the injury.Results. Early (3 hours after the injury) local application of HA for CI improved microcirculation, increased oxygen consumption, and activated oxidative metabolism in the skeletal muscles, which helped reduce the severity of destructive processes in the damaged area. The most effective injection mode was two-fold administration of HA: 3 hours after the compression cessation and additionally 24 hours after the injury.Conclusion. In the crush injury, early local intramuscular injection of HA into the damaged area in the first few hours after the cessation of compression is a sanogenetically substantiated method for correcting traumatic ischemia of the muscles.